2019
DOI: 10.1002/acm2.12610
|View full text |Cite
|
Sign up to set email alerts
|

Transit and non‐transit 3D EPID dosimetry versus detector arrays for patient specific QA

Abstract: Purpose Despite their availability and simplicity of use, Electronic Portal Imaging Devices (EPIDs) have not yet replaced detector arrays for patient specific QA in 3D. The purpose of this study is to perform a large scale dosimetric evaluation of transit and non‐transit EPID dosimetry against absolute dose measurements in 3D. Methods After evaluating basic dosimetric characteristics of the EPID and two detector arrays (Octavius 1500 and Octavius 1000SRS), 3D dose distributions for 68 VMAT arcs, and 10 IMRT pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 41 publications
(92 reference statements)
0
33
0
1
Order By: Relevance
“…Moreover, it is often not possible to use these in combination with Intensity Modulated Radiation Therapy (IMRT) or Volumetric Modulated Arc Therapy (VMAT) for which verification is limited to pre-treatment solutions. Since Electronic Portal Imaging Device (EPID) images contain dose information, many groups have investigated their use for radiotherapy dose measurement [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] . Pre-treatment dose verification and in-vivo dosimetry using EPIDs has become routine practice in a growing number of clinics in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is often not possible to use these in combination with Intensity Modulated Radiation Therapy (IMRT) or Volumetric Modulated Arc Therapy (VMAT) for which verification is limited to pre-treatment solutions. Since Electronic Portal Imaging Device (EPID) images contain dose information, many groups have investigated their use for radiotherapy dose measurement [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] . Pre-treatment dose verification and in-vivo dosimetry using EPIDs has become routine practice in a growing number of clinics in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…For example, thermoluminescent detectors (TLDs) are only capable of point measurement (measuring of the dose on the patient's skin) and films are limited to two‐dimensional (2D) measurements. Recent studies have demonstrated the use of electronic portal imaging devices (EPIDs) as 3D patient‐specific dosimetry tools; however they are associated with uncertainties in the calibration process along with uncertainties in various steps of the dose reconstruction process . Therefore, the implementation of adaptive radiotherapy is limited by the lack of a real‐time device that can accurately measure the delivered dose to the patient …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the use of electronic portal imaging devices (EPIDs) as 3D patient-specific dosimetry tools; 8,9 however they are associated with uncertainties in the calibration process along with uncertainties in various steps of the dose reconstruction process. 10,11 Therefore, the implementation of adaptive radiotherapy is limited by the lack of a real-time device that can accurately measure the delivered dose to the patient. 3,7,12 The x-ray acoustic (XA) effect has recently been proposed as a method for real-time 3D in-vivo dosimetry using x-ray acoustic computed tomography (XACT).…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of a dose or fluence map, taking into account the patient's body, is called transit dosimetry. 11 The aforementioned common use of portal matrices allows to check the dose distribution by measuring fluence maps before the therapeutic session without the patient. [12][13][14] The parameter adopted for comparing two data sets, including dose distributions or fluence maps, is the gamma coefficient.…”
Section: Introductionmentioning
confidence: 99%